Venture capital: opportunities to use foreign investment experience in Russia - A. O. Ovcharov; T. N. Ovcharova; N. O. Marenov (Вестник университета)
The foreign experience of venture investment in the context of the possibilities of its use in Russia is considered in the article. Separate interpretations of venture capital are shown; the role of venture capital funds in investment is indicated. The major stages of the global venture capital investment market development are briefly analysed. The major stages of the global venture capital investment market development are briefly analysed. Two organisational models of making risky investments used in world practice are allocated: limited partnership and evergreen funds. An assessment of the current state of the venture capital industry in the Russian Federation is given, key problems are identified. A number of measures to improve the state mechanism for supporting the venture capital market is proposed. Special attention is paid to legal regulation measures.